Endoscopic transnasal approach to medial orbital lesions - Tan, Sien Hui; Prepageran, Narayanan (Royal Society of Medicine, 2015)
This case report presents our experience of endoscopic transnasal management of medial intra-and extraconal lesions. Case report: An endoscopic transnasal approach to intra-orbital lesions was used for nine patients. Four patients had intraconal lesions and five had lesions in the extraconal space. Post-operatively, seven patients reported an improvement in visual acuity and two reported stable vision. There were no complications of cerebrospinal leakage or diplopia. Conclusion: This case series demonstrated the safety and effectiveness of an endoscopic transnasal approach to managing intraconal and extraconal lesions. This minimally invasive technique should be considered a valid alternative for accessing orbital tumours, particularly those located in the medial compartment.